2020
DOI: 10.3390/ijerph17207658
|View full text |Cite
|
Sign up to set email alerts
|

Association between Neighborhood Food Environment and Body Mass Index among Older Adults in Beijing, China: A Cross-Sectional Study

Abstract: Objective: To investigate the association between the neighborhood food environment and body mass index (BMI) among Chinese older adults. Methods: A multi-stage stratified random sampling method was used to recruit participants from 12 communities in Beijing, China, in 2019. Participants (n = 1764, 1034 women) in this study were older adults aged 65 to 80. We collected the participants’ basic information, measured their height and weight, and calculated their BMI. Neighborhood food environments were measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Some studies have also used data at the individual level by questionnaires or surveys. However, the data are generally from one region, and the results are not generalizable to all of China [13,51]. Our data are from 85 cities and 23 provinces, which reflects the universal situation in China.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Some studies have also used data at the individual level by questionnaires or surveys. However, the data are generally from one region, and the results are not generalizable to all of China [13,51]. Our data are from 85 cities and 23 provinces, which reflects the universal situation in China.…”
Section: Discussionmentioning
confidence: 82%
“…Xu et al found that community exposure to Western fast-food restaurants was positively associated with adults' body weight status in the rural population, and this association was temporally dynamic [50]. Using cross-sectional data in 2019 and adjusted multiple linear regression, Zhang et al identified some significant associations between the neighborhood food environment and obesity in older Chinese adults 65 to 80 years of age [51]. In summary, we found no evidence in China on the associations between fast-food restaurants and obesity specifically in preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…The current study also showed that, the construction of large supermarkets around the neighborhood may improve the dietary diversity of the elderly. However, our previously published research found that supermarkets may be related to the high BMI of the elderly ( 17 ). Therefore, it is important to improve the consumption environment inside the supermarkets and educate the elderly to choose healthy food.…”
Section: Discussionmentioning
confidence: 98%
“…There are many methods to measure the neighborhood food environment, such as questionnaire or phone survey, commercial data list, and Geographic Information System (GIS) Technology ( 17 ). The Baidu Map Application Programming Interface (API) (Baidu, Beijing, China) used to be widely used in fields of transportation, surveying, and mapping engineering ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the past three decades, the dietary intake of Chinese people has changed substantially ( 3 , 30 ), and the current dietary structure is unreasonable. Combined with the unhealthy lifestyle factors of insufficient physical activity, smoking, and excessive drinking, the problems of overweightness, obesity, and diet-related chronic diseases are becoming increasingly more serious in China ( 31 , 32 ). Obesity increases the risk of many chronic diseases, such as hypertension, cardiovascular disease, and diabetes.…”
Section: Discussionmentioning
confidence: 99%